2000
DOI: 10.1136/heart.83.3.289
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal ventricular conduction following dothiepin overdose simulating acute myocardial infarction

Abstract: Objective-To determine whether pharmacological stress leads to prolonged but reversible left ventricular dysfunction in patients with coronary artery disease, similar to that seen after exercise. Design-A randomised crossover study of recovery time of systolic and diastolic left ventricular function after exercise and dobutamine induced ischaemia. Subjects-10 patients with stable angina, angiographically proven coronary artery disease, and normal left ventricular function. Interventions-Treadmill exercise and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…ST segment elevation was reported in leads of DI, aVL, V1 and V2 mimicking a current of anteroseptal subepicardial injury after amitriptyline overdose, which persisted for four days. Serial cardiac enzyme estimates did not confirm an ischaemicevent Steeds & Muthusamy (2000) reported a case of dothiepin (sulphur‐containing analogue of amitriptyline) overdose with a symmetrical T wave repolarization; abnormalities appeared within 9 hr and mimicked acute anteroseptal myocardial infarction. ECG changes persisted for 6 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…ST segment elevation was reported in leads of DI, aVL, V1 and V2 mimicking a current of anteroseptal subepicardial injury after amitriptyline overdose, which persisted for four days. Serial cardiac enzyme estimates did not confirm an ischaemicevent Steeds & Muthusamy (2000) reported a case of dothiepin (sulphur‐containing analogue of amitriptyline) overdose with a symmetrical T wave repolarization; abnormalities appeared within 9 hr and mimicked acute anteroseptal myocardial infarction. ECG changes persisted for 6 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, there has been only one previous report of myocardial infarction due to a tricyclic antidepressant overdose [4]. Previous reports of transient QRS changes which mimic an acute myocardial infarction [5,6] may be either due to quinidine-like effect of dothiepin or to an alteration in membrane permeability rather than due to ischaemic changes of the myocardium itself.…”
mentioning
confidence: 79%
“…Electrocardiographic changes suggestive for myocardial infarction were described in the literature 17,19 in the acute poisoning with dothiepin, although Steeds considers that the cause was the blockade of potassium and rapid sodium channels rather than a real myocardial injury.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 These cases were diagnosed using electrocardiographic records and elevated cardiac enzymes. Other studies reported either electrocardiographic signs of ischemia 17,18,19 or elevated myocardial cytolysis enzymes, 20 but none of these findings were associated with myocardial necrosis.…”
Section: Introductionmentioning
confidence: 96%